Copper powder wick and preparation method thereof
By oxidizing and reducing the water-atomized copper powder, semi-reduced copper powder is formed and sintered in a high-temperature reduction atmosphere, the problem of insufficient capillary climbing rate and porosity of the copper powder absorbent core in the prior art is solved, and the problem of insufficient capillary climbing rate and porosity of the copper powder absorbent core is realized. Preparation of liquid absorbent cores with high thermal conductivity and tensile strength.
Patent Information
- Application Number
- CN202411368942.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The prior art is difficult to use low-cost copper powder to prepare liquid absorbent cores with high capillary climbing rate, high porosity and high tensile strength in industrial heat pipe manufacturing, especially under the higher requirements for heat pipe thermal conductivity in the 5G era. .
By oxidizing the water-atomized copper powder and reducing it below the oxidation temperature, semi-reduced copper powder is formed, and then sintered in a high-temperature reduction atmosphere to form a copper powder liquid absorbing core with surface reduction pores and internal micropores.
The high porosity and capillary climbing rate of the liquid absorbent core are improved, while ensuring the sintering strength of the liquid absorbent core, preventing the liquid absorbent core from breaking during the heat pipe preparation process, and meeting the needs of high thermal conductivity.
Smart Images

Figure CN119407176A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material preparation, and in particular to a method for improving the capillary climbing rate and porosity of a copper powder liquid wick. Background Art
[0002] With the advent of the 5G era, electronic devices are developing towards miniaturization, integration, and higher operating frequencies. The heat generated per unit volume can reach 10 times or even higher than that of 4G devices. Cooling modules with heat pipes are often used in engineering to conduct away the heat of electronic devices. Therefore, higher requirements are placed on the thermal conductivity limit of heat pipes.
[0003] It is usually desirable to use copper powder wicks with higher porosity and higher capillary climbing rate to prepare "copper-water sintered heat pipes" to make the heat pipe thermal conductivity capillary limit stronger. The capillary limit of a heat pipe is proportional to the amount of capillary reflux water. A capillary wick with high porosity absorbs more liquid and has a larger capillary reflux water volume. At the same time, a wick with high capillary climbing rate has a higher capillary reflux speed, which is also beneficial to improving the capillary limit of the heat pipe. A copper powder wick with high capillary climbing rate and high porosity is the basis for the preparation of heat pipes with high thermal conductivity. During the preparation of the heat pipe, the outer copper powder is pulled when bent and is prone to fracture, which causes the working liquid to be cut off at the fracture of the wick, greatly affecting the capillary performance of the heat pipe and causing the thermal conductivity of the heat pipe to drop sharply. Therefore, the wick is also required to have sufficient tensile strength.
[0004] It should be noted that the wicks sintered from different types of copper powders have different capillary climbing rates, porosity and mechanical properties. Generally, the wicks obtained by sintering copper powders with lower bulk density have higher capillary climbing rates and porosity, but the tensile strength of the wicks is reduced; the smaller the particle size of the copper powder, the higher the capillary climbing rate, but the porosity is reduced. Copper powders with lower bulk density are more suitable for preparing high-power heat pipes, but there is a limit to the bulk density of copper powders prepared by water atomization. Many researchers and engineers have begun to develop some copper powder post-processing processes to obtain copper powders with different properties to prepare heat pipes with better thermal conductivity. There are currently two main copper powder processing processes, one is to mix and sinter different types of copper powders, and the other is to add pore-forming agents.
[0005] Chinese patent CN201610781175.X obtains thermal conductive copper powder by mixing copper oxide powder and electrolytic copper powder, sintering and crushing them, and its bulk density can reach 1.6 g / cm 3 The prepared wick has a porosity of 57-80% and a high capillary climbing rate of 13 s / 100 mm. The unique dendritic structure of electrolytic copper powder is mainly used to greatly improve the capillary climbing rate, but due to the high cost of electrolytic copper powder, it is not conducive to large-scale industrial production.
[0006] Chinese patent CN202110799135.9 mixes and sinters 10% to 60% of non-dense copper powder (core-shell copper powder generated by oxidation-reduction) and 40% to 90% of dense copper powder (copper powder not subjected to oxidation-reduction treatment). The bulk density of the copper powder raw material used is 2.4 g / cm 3 , the copper powder particle size is 60-250μm, the porosity of the obtained absorbent core is 50%~57.9%, and the capillary climbing rate is 38.0~46.9 s / 100 mm. The general sintering is to heat up with the furnace. This heating method will cause the surface microporous structure to disappear. Therefore, the porosity of the absorbent core obtained by this method is not high, and the capillary climbing rate is also low, which cannot meet the needs of industrial applications.
[0007] The document "Cheng Qijun. Preparation of copper-based porous core materials for sintered heat pipes and research on their microstructure and properties [D]. Central South University, 2011." reported that the use of pore-forming agents such as CuCl2·2H2O to increase the porosity of the liquid-absorbing core can increase the porosity of the ball powder by about 7%, but the addition of pore-forming agents greatly reduces the strength of the sintered core.
[0008] In engineering applications, the process is expected to be simple. Water-atomized copper powder is commonly used as a filling powder in heat pipes because it is cheaper than electrolytic copper powder. In the context of the 5G era, the flattened thickness of heat pipes is getting thinner and thinner, and the bending angle of heat pipes is more demanding. It is expected that the sintered wick has a certain tensile strength to prevent the wick from breaking during the preparation of the heat pipe. When the external dimensions of the heat pipe are required to be extreme, the powder strength is not expected to decrease, and the pore-forming agent method is no longer applicable. Therefore, in the manufacture of industrial heat pipes, the key to the current problem is how to use a low-cost, simple copper powder post-processing process that significantly improves the performance of the heat pipe to obtain a wick with a high capillary climbing rate, high porosity, and greater tensile strength. Summary of the invention
[0009] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for improving the capillary climbing rate and porosity of a copper powder liquid absorbent core. The water-atomized copper powder is first subjected to sufficient oxidation treatment, and then the oxidized copper powder is reduced at a temperature lower than the oxidation temperature to form a semi-reduced copper powder with surface reduction and residual oxygen elements inside. The semi-reduced copper powder is sintered in a reducing atmosphere to obtain a copper powder liquid absorbent core with high porosity and high capillary climbing rate. The core idea of the present invention is that the reduced parts on the surface of the semi-reduced copper powder contact each other during the sintering process, and a sintering neck can be formed in the first time. When the copper oxide is reduced to pure copper, heat is released, which is conducive to forming a liquid absorbent core with high sintering strength, and the problem of the liquid absorbent core breaking during the preparation of the heat pipe is prevented; the oxygen element remaining in the semi-reduced copper powder is used to delay the sintering process, reduce the shrinkage rate of the liquid absorbent core, and prevent over-sintering, so as to obtain a liquid absorbent core with high porosity; the sintering parameters are adjusted so that the rough structure formed by the escape of the residual oxygen element in the interior during the reduction process is retained, and the surface of the liquid absorbent core after sintering has reduced pores, which is conducive to improving the capillary climbing rate of the liquid absorbent core, and obtaining a liquid absorbent core with a high capillary climbing rate.
[0010] In order to achieve the above technical effects, the present invention adopts the following technical solutions: A method for preparing a copper powder liquid wick comprises the following steps: Step 1: oxidize the water-atomized copper powder raw material in an air atmosphere at a temperature not lower than 400° C. for more than 30 min, and the mass increase percentage after oxidation is more than 3%; Step 2: first raise the temperature to the reduction temperature, then put in the copper powder, and perform surface reduction in a reducing atmosphere, the reduction temperature is 350-600°C, the time is 10-20 min, and the reduction temperature is lower than the oxidation temperature of step 1 (not completely reduced, to ensure that only the oxygen elements on the surface of the copper powder are reduced, and the oxygen elements inside remain). After reduction, the surface of the copper powder is glossy, and some oxygen elements remain inside. The mass of the copper powder after oxidation and reduction increases by more than 1% compared with the mass of the copper powder raw material; Step 3: After the sintering furnace is heated to above 650°C, the copper powder after oxidation and reduction is put in. The subsequent sintering furnace heating rate is 8~15°C / min. Sintering in a reducing atmosphere above 800°C for 20~60 min can obtain the copper powder wick. The copper powder sintering in step 3 should have a large heating rate. This method is the key to the formation of microporous rough structure on the surface of the copper powder. The reason is that the reduction temperature of the oxidized copper powder is much lower than the sintering temperature of the copper powder. If the copper powder is heated with the furnace temperature, the residual oxygen inside the copper powder obtained in step 2 will be reduced first, and the effect of reducing the sintering shrinkage rate is not obvious. In addition, the formed micropores are very easy to fuse and disappear in the subsequent sintering process, and the purpose of forming reduced micropores to increase the capillary climbing rate cannot be achieved.
[0011] The sintering time of copper powder should not be too long, otherwise the generated reduction pores cannot be retained, and the purpose of increasing the capillary climbing rate cannot be achieved. After the copper powder is sintered, if there is no powder falling, it can be considered as a successful sintering. In the case of successful sintering, the sintering time should be reduced to ensure sufficient micropores remain.
[0012] Preferably, the bulk density of the water atomized copper powder is 1.7-2.2 g / cm 3 , particle size is 50~100 mesh.
[0013] Preferably, the oxidation temperature of step one is 450-700° C., the oxidation time is 40-120 min, the mass increase percentage after oxidation is 6%-20%, and through energy spectrum EDS testing, the mass percentage of oxygen on the surface of the copper powder after oxidation is 15%-25%, which basically reaches the limiting oxygen storage capacity of copper.
[0014] Preferably, the reduction temperature in step 2 is at least 50° C. lower than the oxidation temperature in step 1, and the mass increase percentage of the treated copper powder compared to the copper powder raw material is 1% to 5%.
[0015] Preferably, step 1 adopts dynamic oxidation to prevent the copper powder from sintering into agglomerates.
[0016] Preferably, the dynamic oxidation is to oxidize the copper powder for 20±10 min, stir the copper powder to a loose state after cooling, and then continue oxidation under the same conditions.
[0017] Preferably, in step three, the sintering temperature of the copper powder is 860±40° C., and the mass percentage of oxygen in the sintered liquid wick tested by EDS spectrum is less than 0.5%.
[0018] Preferably, the reducing atmosphere in step 2 and step 3 is a nitrogen-hydrogen mixed gas, wherein the mass percentage of hydrogen is 5%; and the sintering time in step 3 is 30±10 min.
[0019] Preferably, the oxidation temperature in step one is 500±100°C, the reduction temperature in step two is 400±100°C, and the copper powder feed temperature in step three is 100-200°C lower than the sintering temperature.
[0020] The principle of the present invention is: using copper powder with a certain amount of oxygen remaining inside for sintering, compared with pure copper powder sintering, its sintering shrinkage is lower, the porosity of the liquid absorbent core is larger, the capillary climbing rate is larger, and it has a considerable tensile strength of the sintered body. The oxidized copper powder has a high melting point. If it is directly sintered at the original temperature, the sintering neck formation rate is extremely low, and the obtained liquid absorbent core has a low tensile strength, is easy to break, and is easy to lose powder; if the surface of the oxidized copper powder is reduced, it is conducive to the formation of the sintering neck, that is, it ensures a considerable tensile strength of the sintered body, and the residual oxygen inside can also play a role in delaying the sintering rate, thereby reducing the sintering shrinkage and increasing the porosity of the sintered body; during the sintering process, the residual oxygen elements inside the copper powder are reduced to form micropores, and the micropores can be retained under appropriate sintering process parameters, which can increase the roughness of the copper powder surface and is conducive to improving the capillary climbing rate of the liquid absorbent core.
[0021] Compared with the prior art, the present invention has the following advantages: 1) The present invention does not require the use of pore-forming agents, electrolytic copper powder and other auxiliary raw materials, and can achieve significant improvement in the porosity of the liquid-absorbing core and the capillary climbing rate, and has the advantages of simple process and low cost.
[0022] 2) The copper powder sintered liquid absorbent core obtained by the method of the present invention exhibits higher porosity and stronger capillary action. 3 , 70~80 mesh copper powder raw materials, according to the post-treatment process, the shrinkage rate of the wick can be reduced by up to 6%, the porosity can be increased by up to 5.93%, and the capillary climbing rate can be increased from 27.0 s / 100 mm to 17.9 s / 100 mm.
[0023] 3) The present invention adopts a large temperature increase range for sintering, such as adding copper powder for sintering after the furnace temperature reaches 700°C, which successfully retains the pore structure generated by the reduction process, is simple to operate, and has a significant effect on improving the capillary climbing rate.
[0024] 4) The porosity of the copper powder wick of the present invention is continuously adjustable, and the porosity is limited by the hindering effect of oxygen on the sintering process. The deeper the residual depth of oxygen and the higher the residual content of oxygen, the greater the porosity of the wick. That is, when other parameters are the same, at the same oxidation temperature, the lower the reduction temperature, the greater the porosity of the wick; at the same reduction temperature, the higher the oxidation temperature, the greater the porosity of the wick.
[0025] 5) The present invention ensures sufficient sintering strength of the liquid wick, effectively prevents the problem of the liquid wick breaking during the preparation process of the heat pipe, and ensures stable performance of the heat pipe. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a low-magnification scanning electron microscope image of the copper powder raw material used in Examples 1 to 5.
[0027] Figure 2 This is a high-magnification scanning electron microscope image of the copper powder raw material used in Examples 1 to 5.
[0028] Figure 3 This is the surface morphology of the copper wick directly sintered from the copper powder raw material in Example 1.
[0029] Figure 4 This is the surface morphology of the copper powder in Example 2 after oxidation.
[0030] Figure 5 This is the surface morphology of the copper powder in Example 2 after oxidation-reduction.
[0031] Figure 6 This is the surface morphology of the copper powder after sintering that has been subjected to oxidation-reduction treatment in Example 2.
[0032] Figure 7 This is the surface morphology of the copper powder in Example 3 after oxidation.
[0033] Figure 8 This is the surface morphology of the copper powder in Example 3 after oxidation-reduction.
[0034] Fig. 9 This is the surface morphology of the copper powder after sintering after oxidation-reduction treatment in Example 3.
[0035] Fig.10 The tensile strength distribution diagram of the absorbent cores of Examples 1 to 5 is shown in FIG. DETAILED DESCRIPTION
[0036] The present invention is further described below by way of examples, and the scope of protection claimed in the present invention is not limited to the scope represented by the examples.
[0037] In this example, the bulk density used is 2.08 g / cm 3 , 70~80 mesh copper powder as raw material, powder morphology photo as shown Figure 1 and Figure 2 shown.
[0038] The test method of bulk density is based on GB / T 1479.1-2011 "Determination of bulk density of metal powders Part 1: Funnel method"; the copper powder used is obtained by sieving, and 70-80 mesh copper powder is used in the embodiment to obtain more stable and reliable results.
[0039] The porosity and shrinkage test methods are as follows: a powder cake block is sintered in a graphite box with an inner chamber diameter of 25 mm and a depth of 8 mm; the porosity of the powder cake is calculated using the density method, and the shrinkage rate of the powder cake diameter is taken as the shrinkage rate.
[0040] The capillary climbing rate test method is: put a 100 mm long and 20 mm wide copper powder sintered body into 10 mm deep pure water, record the time for the water to rise to the top, as the height of the wick increases, the capillary climbing rate is slower, and "27.0 s / 100 mm" indicates that the capillary climbing rate is appropriate. At present, there is no standard method for the capillary climbing rate test method of the copper powder wick, and the test method used in the present invention is similar to the literature patent and has good comparability.
[0041] The tensile strength test method is as follows: a cylindrical liquid-absorbing core sintered by a graphite mold with an inner chamber diameter of 10 mm and a depth of 150 mm is tested using a universal mechanical testing machine.
[0042] All data are the average of the test results of three samples, and all samples are prepared from the same batch to ensure that the sample preparation conditions are absolutely the same.
[0043] Example 1 Example 1 was used as a control group experiment, and copper powder raw materials were directly sintered. Figure 3 The microscopic surface morphology of the copper powder wick is shown, with a smooth surface and rounded corners.
[0044] Operation steps: sinter the copper powder raw material in a tube furnace at 860℃, nitrogen and hydrogen mixed gas flow rate 20 L / min, for 30 minutes, the copper powder inlet temperature is 700℃ (heating rate is 10℃ / min), and the target product can be obtained after cooling to room temperature. Its sintering shrinkage is 9.32%, the wick porosity is 57.36%, and the capillary climbing rate is 27.0 s / 100 mm.
[0045] Example 2 A method for improving the capillary climbing rate and porosity of a copper powder wick, comprising the following steps: Step 1: Oxidize the copper powder in a tube furnace at 450°C and an air flow rate of 50 L / min for 20 min. After cooling, stir the copper powder until it is loose and then oxidize it under the same conditions for 40 min. This effectively prevents the formation of sintering necks. The mass increase of the copper powder after oxidation is 6.04%. Figure 4 The microscopic surface morphology of the oxidized copper powder obtained is shown.
[0046] Step 2: The copper powder obtained in step 1 was reduced in a tube furnace at 350°C and a nitrogen-hydrogen mixed gas flow rate of 20 L / min for 10 min. Compared with the copper powder raw material, the mass increase percentage after oxidation-reduction was 2.19%, and the surface of the copper powder showed luster. Figure 5 Shows the microscopic surface morphology of incompletely reduced copper powder.
[0047] Step 3: Sinter the copper powder obtained in step 2 in a tubular furnace at 860°C and a nitrogen-hydrogen mixed gas flow rate of 20 L / min for 30 min. The copper powder inlet temperature is 700°C (heating rate is 10°C / min). After cooling to room temperature, the target product can be obtained.
[0048] According to EDS test, the mass percentage of oxygen on the surface of copper powder after oxidation is 18.7%, the mass percentage of oxygen on the surface of copper powder after reduction is 2.53%, and the mass percentage of oxygen on the surface of copper powder after sintering is less than 0.2%. Figure 6 The microscopic surface morphology of the sintered copper powder is shown, with residual reduced microporous (~2 um) structure.
[0049] The tests showed that the porosity of the copper powder sintered body was 59.76%, the sintering shrinkage was 7.93%, and the capillary climbing rate of the wick was 21.4 s / 100 mm.
[0050] Example 3 A method for improving the capillary climbing rate and porosity of a copper powder wick, comprising the following steps: Step 1: Oxidize the copper powder in a tube furnace at 550°C and air flow rate of 50 L / min for 20 min. After cooling, stir the copper powder to a loose state and oxidize it under the same conditions for 40 min. This effectively prevents the formation of sintering necks. The mass increase of the copper powder after oxidation is 9.61%. Figure 7 The microscopic surface morphology of the oxidized copper powder obtained is shown.
[0051] Step 2: The copper powder obtained in step 1 was reduced in a tube furnace at 400°C and a nitrogen-hydrogen mixed gas flow rate of 20 L / min for 10 min. Compared with the copper powder raw material, the mass increase percentage after oxidation-reduction was 3.51%, and the surface of the copper powder showed luster. Figure 8 Shows the microscopic surface morphology of incompletely reduced copper powder.
[0052] Step 3: Sinter the copper powder obtained in step 2 in a tubular furnace at 860°C and a nitrogen-hydrogen mixed gas flow rate of 20 L / min for 30 min. The copper powder inlet temperature is 700°C (heating rate is 10°C / min). After cooling to room temperature, the target product can be obtained.
[0053] According to EDS test, the mass percentage of oxygen on the surface of copper powder after oxidation is 19.9%, the mass percentage of oxygen on the surface of copper powder after reduction is 2.13%, and the mass percentage of oxygen on the surface of copper powder after sintering is less than 0.2%. Fig. 9 The microscopic surface morphology of the sintered copper powder is shown, showing a large number of reduced micropores (~2 um) and a small number of cracks.
[0054] The test shows that the porosity of the copper powder sintered body is 63.29%, the sintering shrinkage is 5.27%, and the capillary climbing rate of the copper powder sintered body is 17.9 s / 100 mm, that is, it takes 17.9 s for the capillary to climb 100 mm.
[0055] Compared with Example 2, in Example 3, the oxidation and reduction temperatures are higher, the mass percentage of residual oxygen elements is higher, the residual depth of oxygen elements is deeper, the delaying effect on sintering is stronger, the sintering shrinkage rate is smaller, and more reduction micropores formed during the sintering process are retained, which increases the capillary climbing rate of the wick.
[0056] Example 4 A method for improving the capillary climbing rate and porosity of a copper powder wick, comprising the following steps: Step 1: Oxidize the copper powder in a tube furnace at 550°C and an air flow rate of 50 L / min for 20 min. After cooling, stir the copper powder to a loose state and then oxidize it under the same conditions for 40 min. This effectively prevents the formation of sintering necks. The mass increase percentage of the copper powder after oxidation is 9.61%.
[0057] Step 2: The copper powder obtained in step 1 was reduced in a tube furnace at 500°C and a nitrogen-hydrogen mixed gas flow rate of 20 L / min for 10 min. Compared with the copper powder raw material, the mass increase percentage after oxidation-reduction was 2.04%, and the surface of the copper powder showed luster.
[0058] Step 3: Sinter the copper powder obtained in step 2 in a tubular furnace at 860°C (heating rate of 10°C / min) and a nitrogen-hydrogen mixed gas flow rate of 20 L / min for 30 min. The copper powder inlet temperature is 700°C. After cooling to room temperature, the target product can be obtained.
[0059] The test showed that the porosity of the copper powder sintered body was 60.86%, the sintering shrinkage was 6.77%, and the capillary climbing rate of the wick was 18.7 s / 100 mm.
[0060] Compared with Example 3, in Example 4, the reduction temperature is higher, the mass percentage of residual oxygen element is lower, and the delaying effect on sintering is weaker, so the sintering shrinkage rate is larger, and the reduced pore structure can be well retained, resulting in a capillary climbing rate comparable to that of Example 3.
[0061] Example 5 Example 5 illustrates the necessity of reducing the oxidized copper powder, and the implementation steps are as follows: Step 1: Oxidize the copper powder in a tube furnace at 550°C and an air flow rate of 50 L / min for 20 min. After cooling, stir the copper powder to a loose state and then oxidize it under the same conditions for 40 min. This effectively prevents the formation of sintering necks. The mass increase percentage of the copper powder after oxidation is 9.61%.
[0062] Step 2: Sinter the copper oxide powder obtained in step 1 in a tubular furnace at 860°C (heating rate of 10°C / min) and a nitrogen-hydrogen mixed gas flow rate of 20L / min for 30 min. The copper powder inlet temperature is 700°C. After cooling to room temperature, the target product can be obtained.
[0063] After testing, the shrinkage rate of the copper powder sintered body is extremely low, at 3.35%. There is black unreduced copper oxide powder in the sintered block, the sintering neck is not formed in large quantities, the sintering strength is low, the powder is easy to fall off, and it cannot be used.
[0064] For special pore structures such as wicks, the tensile strength test results are relatively discrete, such as Fig.10 As shown, the tensile strength of the samples obtained in Examples 1 to 4 is 1.81 to 3.23 MPa. The average tensile strength of Example 2 obtained by the test is the largest, which is 2.73 MPa, and the average tensile strength of Example 1 is 2.53 MPa, which shows that after being treated by the present invention, the tensile strength of the wick is basically not weakened; the tensile strength of Example 5 is all below 1.59 MPa, which fully illustrates that after the copper powder with unreduced surface is sintered, the tensile strength decreases significantly, which will cause the problem of split fracture in the preparation process of the heat pipe.
[0065] Table 1 Process parameters of Examples 1 to 5 and performance test results of products (average values) The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a copper powder liquid wick, characterized in that: The following steps are involved: Step 1: oxidize the water-atomized copper powder raw material, and the mass increase percentage after oxidation is more than 3%; Step 2: first raise the temperature to the reduction temperature, then put in the copper powder, and perform surface reduction in a reducing atmosphere, the reduction temperature is 350-600°C, the time is 10-20 min, and the reduction temperature is lower than the oxidation temperature of step 1. After reduction, the surface of the copper powder is glossy, and some oxygen elements remain inside. After oxidation and reduction, the mass of the copper powder increases by more than 1% compared with the mass of the copper powder raw material; Step 3: After the sintering furnace is heated to above 650°C, the oxidized and reduced copper powder is put in. The subsequent sintering furnace heating rate is 8~15°C / min. Sinter in a reducing atmosphere above 800°C for 20~60 min to obtain the copper powder liquid wick.
2. The preparation method according to claim 1, characterized in that: The bulk density of the water atomized copper powder is 1.7-2.2 g / cm 3 , particle size is 50~100 mesh.
3. The preparation method according to claim 1, characterized in that: The oxidation temperature of step one is 450-700°C, the oxidation time is 40-120 min, the mass increase percentage after oxidation is 6%-20%, and the mass percentage of oxygen on the surface of the copper powder after oxidation according to EDS test is 15%-25%.
4. The preparation method according to claim 3, characterized in that: The reduction temperature in step 2 is at least 50° C. lower than the oxidation temperature in step 1, and the mass increase percentage of the treated copper powder compared to the copper powder raw material is 1% to 5%.
5. The preparation method according to claim 4, characterized in that: Step one uses dynamic oxidation.
6. The preparation method according to claim 5, characterized in that: The dynamic oxidation is to oxidize the copper powder for 20±10 minutes, stir the copper powder to a loose state after cooling, and then continue oxidation under the same conditions.
7. The preparation method according to any one of claims 1 to 6, characterized in that Step 3: The sintering temperature of the copper powder is 860±40°C, and the mass percentage of oxygen in the sintered liquid wick tested by EDS spectrum is less than 0.5%.
8. The preparation method according to claim 7, characterized in that: The reducing atmosphere in step 2 and step 3 is a nitrogen-hydrogen mixture, in which the mass percentage of hydrogen is 5%; the sintering time in step 3 is 30±10 min.
9. The preparation method according to claim 8, characterized in that: The oxidation temperature in step one is 500±100°C, the reduction temperature in step two is 400±100°C, and the copper powder feed temperature in step three is 100~200°C lower than the sintering temperature.
10. The copper powder liquid wick prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A thermally conductive copper powder with high capillary velocity and low bulk density and preparation method thereof
CN106238725B
A copper powder, its preparation method, and a capillary core made from the copper powder.
CN113245543B
Method for manufacturing micro heat pipe by reducing copper oxide powder
CN104759627A
Copper powder, preparation method thereof and capillary core prepared from copper powder
CN113245543A
Liquid absorption core, phase change heat transfer device and preparation method
CN114406266A